Performance of free prostate-specific antigen ratio in differentiating between prostatic cancer and benign prostatic lesions at a referral hospital in South Africa - Boitumelo Phiri-Ramongane; Ayeaye Khine (South African Family Practice)
Background: Prostate cancer is a leading cause of morbidity and mortality in our male population, thus screening initiatives will help to improve outcomes. The current screening marker, total prostate-specific antigen (PSA), is not prostate cancer specific. The development of percentage free PSA (%FPSA) has largely improved the detection of prostate cancer. Objectives: To assess the performance of %FPSA ratio at the 25% cut-off and its ability to distinguish between prostate cancer and benign prostatic lesions. Methods: This was a retrospective study conducted on male patients with total prostate-specific antigen values 10 ng/ml and with prostate histology results. Male patients with total prostate-specific antigen between 4 and 10 ng/ml had their free prostate-specific antigen determined together with the calculation of the free prostate-specific antigen ratio. The ratio was then correlated with prostate histology results to determine the presence of prostate cancer at the cut-off ratio of 25%. Results: Prostate cancer was detected in 28 (21.37%) patients out of the total population of 131. Ninety-two patients had a FPSA ratio of 25%, 22 (22.8%) of whom were found to have prostate cancer. Notably the sensitivity and specificity were found to be 86% and 27% respectively, with a positive predictive of value of 21% at this cut-off. Conclusions: The study demonstrates a %FPSA ratio of 25% not to be a good discriminator between prostatic cancerous and benign lesions. It is thus recommended that a prostate biopsy should be done based on clinical examination findings rather than the level of total prostate specific antigen from 0–10 ng/ml or %FPSA ratio.